UTILITY FACTOR ANALYSIS AND COST OWNERSHIP OF THE PLUG-IN HYBRID ELECTRIC VEHICLE (MITSUBISHI OUTLANDER PHEV) - Hanafi Anis Alamri; Iwa Garniwa (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Recently, attention to CO2 or greenhouse gas emissions has increased. The need to reduce it is also increasing in various countries. One of them is by reducing gas emissions from vehicles. Due to increasingly sophisticated technological advances, many vehicle manufacturers worldwide have switched to electric vehicles. In the world, various types of electric vehicle models have been developed, one of which is the Plug-in Hybrid Electric Vehicle or PHEV. In Indonesia, this vehicle is very suitable for your energy conditions because fuel oil is still abundant, and there are many ways to build power plants. The potential of PHEV vehicles to reduce greenhouse gas emissions is highly dependent on the use of the vehicle and its energy sources, namely gasoline and electricity. However, PHEVs' specific benefits or impacts ultimately depend on vehicle buying and usage patterns. Some parameters are the value of the utility factor (UF) and the value of expenditure efficiency when owning a vehicle or Total Cost Ownership (TCO). Comprehensive results by calculating the UF value can help users understand the actual energy consumption more clearly and TCO to determine the expenses incurred by PHEV users. This study will show the UF and TCO values of one of the PHEV vehicles in Indonesia, namely the Mitsubishi Outlander PHEV.